Peran Work Engagement Dalam Menurunkan Turnover Intention Perawat: A Systematic Review - Nisa Dewanti; Kusnanto Kusnanto; Slamet Riyadi Yuwono (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Background: Employees who are engaged will feel satisfied with their work so they feel very involved in their work, and this has a positive effect on improving physical and mental health, improving performance, and reducing the level of absenteeism and turnover intention on employees. Objective: To find out how the role of work engagement is to reduce nurse turnover intention. Method: This systematic review was based on Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). The database used in this studied was Scopus, ScienceDirect, Emerald, PubMed, and Semanticscholars were limited to publications from 2015 to 2020, full-text article and in english. The keywords used were "nurse" AND "work engagement" AND "turnover" OR "intent to leave" OR "intent to stay". This systematic review used 15 articles that fit the inclusion criteria. Results: This systematic review research study proved the role of work engagement in reducing nurse turnover intention. All research proved that work engagement was directly negatively and significantly correlated with turnover intention. In addition to played a direct role, work engagement also acted as a mediator between independent variables and turnover intention. Work engagement could play a role as a full mediator as well as some mediators. Recommendation: Future research can be done to develop a work engagement model as an effort to reduce nurse turnover intention in Indonesia. Keywords: work engagement; turnover intention; intent to stay; nurse ABSTRAK Latar belakang: Karyawan yang engaged akan merasa puas dengan pekerjaan mereka sehingga merasa sangat terlibat dalam pekerjaan mereka, dan hal tersebut menimbulkan efek positif pada peningkatan kesehatan fisik dan mental, peningkatan kinerja, dan mengurangi tingkat absensi serta turnover intention pada karyawan. Tujuan: Untuk mengetahui bagaimana peran dari work engagement untuk menurunkan turnover intention perawat. Metode: Systematic review ini disusun berdasarkan Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Database yang digunakan dalam penelitian ini Scopus, ScienceDirect, Emerald, PubMed dan Semanticscholar terbatas untuk publikasi dari tahun 2015 hingga 2020, full text article dan berbahasa Inggris. Kata kunci yang digunakan adalah “nurse” AND “ work engagement” AND “turnover” OR “intent to leave” OR “intent to stay”. Systematic review ini menggunakan 15 artikel yang sesuai dengan kriteria inklusi Hasil: Studi penelitian systematic review ini membuktikan adanya peran dari work engagement dalam menurunkan turnover intention perawat. Seluruh penelitian membuktikan bahwa work engagement secara langsung berkorelasi negatif dan signifikan terhadap turnover intention. Selain berperan secara langsung, work engagement juga berperan sebagai mediator antara variabel independen dan turnover intention. Work engagagement dapat berperan sebagai mediator penuh maupun mediator sebagian. Rekomendasi: Penelitian selanjutnya dapat dilakukan pengembangan model work engagement sebagai upaya untuk menurunkan turnover intention perawat di Indonesia. Kata kunci: work engagement; turnover intention; intent to stay; perawat